Intelligent System for Monitoring and Optimizing Viticultural Processes - Andrei DANILĂ; Robert STRECHE; Oana ORZA; Cristina DOBRE; George SUCIU (Aerul şi Apa: Componente ale Mediului)
Viticulture faces increasing challenges related to environmental sustainability and operational efficiency. To address these issues, this work presents the development of an innovative management and monitoring platform tailored for vineyard operations. The proposed platform integrates IoT technology and advanced data analysis to optimize viticultural processes. Key features include real-time tracking of machinery, such as tractors, for precise route visualization, as well as the monitoring of important parameters such as CO₂ emissions, fuel consumption, and other operational metrics. By analyzing these parameters, the platform aims to improve resource efficiency and minimize the environmental footprint of vineyard activities. Additionally, the platform incorporates IoT-enabled climatic monitoring systems to gather data on temperature, humidity, and other weather-related variables, ensuring better decision-making for vineyard management. By merging machinery telemetry with environmental monitoring, the platform provides an advanced solution to improve sustainability in viticulture. This approach not only contributes to reducing greenhouse gas emissions but also aligns with modern practices for precision agriculture. Through this initiative, we aim to demonstrate how technology can empower vineyards to achieve higher efficiency while promoting eco-friendly practices.